Comparing the Electromyography Activity of Core Muscles During Side Plank Exercise on Stable and Unstable Surfaces - Farideh Babakhani; Mohamadreza Hatefi (Islamic Azad University, Hamedan Branch, 2019)
Objective Numerous abdominal exercises with Swiss ball are used to improve core stability with strengthening and rehabilitation goals. It is claimed that the stability exercises have a greater impact on core muscle activation, but the validity of this claim is still in doubt. Moreover, there is no comprehensive study on the comparison of the core muscles activity in different core stability exercises. Therefore, the purpose of this study was to compare the Electromyography (EMG) activity of core muscles while performing side plank on stable and unstable (Swiss ball) surfaces. Methods Fifteen male students of Allameh Tabataba'i University were selected for the study based on inclusion and exclusion criteria. The EMG activity of gluteus medius, rectus abdominis, external oblique, and internal oblique muscles in subjects was recorded while performing side plank exercise on a fixed surface and a Swiss ball (2 sets of 5 seconds with a 30-second rest interval). Results There was a significant difference in the EMG activity of gluteus medius, external oblique and rectus abdominis muscles between two conditions of with and without Swiss ball (P<0.05), but no significant difference was observed in the EMG activity of internal oblique muscle (P>0.05). Conclusion Side plank exercise on the unstable surfaces (Swiss balls) can cause changes in the EMG activity of gluteus medius, rectus abdominis and external oblique muscles compared to when the exercise is performed on stable surfaces, and highly involved the pelvic lumbar muscles effective in maintaining core stability. Therefore, the use of side plank exercise on unstable conditions in a progressive program with gradually increased intensity is recommended which can be effective in strengthening and applying effective muscle contractions useful for core stability.